(Invited) Metal-Atom Ionization and Diffusion under Electric Field around Metal/Insulator Interfaces; First-Principles View. (16th August 2017) - Nakayama, Takashi; Asayama, Yoshihiro; Nagasawa, Riki
Abstract : Metal-atom diffusion from electrode into gate insulator often causes serious damages in electronic devices, particularly under electric field during device operation. In this work, we studied how metal atoms are ionized and diffuse under electric field at metal/SiO2 interfaces by the first-principles calculation. It was shown that the ionization of metal atom occurs owing to (i) the breakdown of hybridization with metal-induced gap states (MIGS) and (ii) the electron transfer from metal atom to electrode. Reflecting such ionization, the electric field remarkably decreases the potential barrier and accelerates the diffusion of metal atoms from electrode into SiO2 . Based on the microscopic mechanism of diffusion around the interface, a simple formula using elemental physical quantities is derived to estimate the potential barrier height in electric field.